1999
DOI: 10.1038/sj.sc.3100719
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of immature heterotopic ossification in spinal cord injury with combination surgery, radiation therapy and NSAID

Abstract: Heterotopic ossi®cation (HO) is a frequent complication associated with spinal cord injury. Management of HO consists of a combination of range-of-motion, diphosphonates, nonsteroidal antiin¯ammatory agents, radiation therapy, and in some cases, surgical resection. The appropriate timing of surgical resection has traditionally been based on maturity of the HO. The case presented is that of a 33-year-old male with T8 complete paraplegia who developed HO about the left hip resulting in impaired sitting. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 18 publications
0
24
0
5
Order By: Relevance
“…Di erent preventive protocols have been used, such as etidronate, 24,25 NSAIDs in combination with etidronate and radiation therapy, 26 NSAIDs alone 27,28 or with etidronate. 29 Garland et al used etidronate in nine patients after surgical resection of HO and were not able to determine its bene®ts against recurrence of HO.…”
Section: Discussionmentioning
confidence: 99%
“…Di erent preventive protocols have been used, such as etidronate, 24,25 NSAIDs in combination with etidronate and radiation therapy, 26 NSAIDs alone 27,28 or with etidronate. 29 Garland et al used etidronate in nine patients after surgical resection of HO and were not able to determine its bene®ts against recurrence of HO.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no correlation between NHO recurrence and the time post SCI or NHO onset. 49,174,177 Recently McAuli e et al 170 and Freebourn 177 reported three patients that had successfully undergone early resection of NHO, that is within 7 ± 11 months post SCI. Earlier surgery may be warranted to prevent ®brous ankylosis, muscle contractures, and severe disuse osteoporosis to decrease the intra-operative fracturation rate.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…9 ± 11,24,31 While Stover did not ®nd any correlation between the extent of recurrence and length of onset of HO to surgery, 29 Freebourn stated that early resection of immature HO may not be predictive of a higher recurrence rate. 32 Because HO resection is associated with poor outcome mainly due to a high recurrence rate, di erent prophylactic methods have been developed to reduce the recurrence rate. Both irradiation and indomethacin seem to be e ective in preventing HO occurrence after total hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation may disrupt the di erentiation process of pluripotential mesenchymal cells into osteoblasts. 32,34 It may also serve to decrease pain perception associated with the tissue in¯ammatory reaction around the side of HO, or it may be involved in ablation of pain receptors. 34 Post-operative irradiation has been reported to decrease the recurrence of HO after surgical resection of HO in SCI, but no controlled studies are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation